2011
DOI: 10.1016/j.jalgebra.2011.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fusion systems with parabolic families

Abstract: Let G be group; a finite p-subgroup S of G is a Sylow p-subgroup if every finite p-subgroup of G is conjugate to a subgroup of S. In this paper, we examine the relations between the fusion system over S which is given by conjugation in G and a certain chamber system C, on which G acts chamber transitively with chamber stabilizer N G (S).Next, we introduce the notion of a fusion system with a parabolic family and we show that a chamber system can be associated to such a fusion system. We determine some conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is possibly be an illusion created by considering groups which are is some way small. Evidence that they may be exotic after all comes, for example, from [46] where it is shown that, in certain good situations, a saturated fusion system determines a locally finite classical Tits chamber system and so is not exotic. Work of van Beek generalizing the classification of groups with a weak BN-pair has also not revealed any surprises [55].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…This is possibly be an illusion created by considering groups which are is some way small. Evidence that they may be exotic after all comes, for example, from [46] where it is shown that, in certain good situations, a saturated fusion system determines a locally finite classical Tits chamber system and so is not exotic. Work of van Beek generalizing the classification of groups with a weak BN-pair has also not revealed any surprises [55].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The following proposition is proved using a result of Onofrei [Ono11] which identifies a parabolic system in F, and further restrictions then identify Sp 6 (3) from an associated chamber system. We will not define parabolic systems for fusion systems here, but we remark that in the case of parabolic systems in groups, the definition is meant to abstractly capture a set of minimal parabolics containing a "Borel", in analogy with groups of Lie type in defining characteristic.…”
Section: Thus Z(s) < O 3 (F) and We Deduce Thatmentioning
confidence: 99%
“…In the case of the group G := Co 1 , the groups N G (E i ) for i ∈ {1, 2, 3} all contain the "Borel" N G (S) and together generate G and so successfully form something akin to a parabolic system. Utilized above, work by Onofrei [Ono11] parallels the group phenomena in fusion systems and provides conditions in which a parabolic system within a fusion system F gives rise to a parabolic system in the group sense. The resulting completion of the group parabolic system realizes the fusion system and if certain additional conditions are satisfied, the fusion system is saturated.…”
Section: Thus Z(s) < O 3 (F) and We Deduce Thatmentioning
confidence: 99%